Failure characteristics and the law of the energy evolution of granite with different pre-crack inclination angles under uniaxial compression loading - Zhao, Ercheng; Li, Juhong; Zhang, Xiongtian; Zhang, Chunyang; Ren, Qinglin; Tan, Tao; Wang, Yixian (Frontiers in Earth Science, 2023)
Cracks affect the strength of rock masses and eventually threaten their stability in engineering. In order to study the fracture characteristics and mechanical properties of cracked rocks, uniaxial compression tests of pre-cracked granite samples with a central circular through hole were carried out by using MTS816 rock mechanics testing system. The inclination angles of different pre-cracks are 0°, 15°, 30°, 45°, 60°, 75° and 90° respectively, and the influence of the crack stop hole near the crack tip on the failure behavior of pre-cracked samples is also considered. The results indicate that, compared with the intact sample, the peak strength of pre-cracked samples decreases significantly and is related to the pre-crack inclination angle. The failure mode of the sample varies with the pre-crack inclination angle, and the crack stop hole near the crack tip also has a certain influence on the crack growth to a certain extent. However, in terms of failure mode and its transformation law, the influence of central circular through hole and crack stop hole can be ignored. Generally speaking, the larger the inclination angle of the pre-crack, the more the total energy required for failure of the sample, and the more the stored elastic strain energy. Before the peak strength, the elastic strain energy of the sample is greater than the dissipated energy, after the peak strength, the dissipated energy gradually exceeds the elastic strain energy due to energy conversion. It is found that the pre-crack reduces the energy storage capacity of the sample, and the total energy is ultimately dominated by sample integrity. The dissipated energy rate increases first, then decreases, and finally increases again, the inflection points are the end of micro-crack closure and the peak strength, respectively. The crack stop hole changes the law of energy evolution to a certain extent, which can improve the ability of rocks to accumulate energy when designed at an appropriate position, so as to improve its load-bearing capacity in a certain range. The results display the mechanical properties of pre-cracked granite samples under uniaxial compression and are conducive to its application in engineering.